INDONESIAN LIBRARIANS’ EFFORTS TO ADAPT AND REVISE THE DEWEY DECIMAL CLASSIFICATION (DDC)’S NOTATION 297 ON ISLAM - Basuki, L. Sulistyo; Alit, Sri Mulyani (Malaysian Journal of Library and Information Science, 2017)
In Indonesia, two points must be considered on utilizing notation classification on Islam. One is that Indonesia is the largest Islamic country in the world, in which about 90% of her 220 million populations are Muslims. The other is that Indonesian libraries have been using the Dewey Decimal Classification (DDC) since early 1950s. From Indonesian librarians point of view, the term â€œMohammedanismâ€ used in the 15th edition is not appropriate that and the notation given is very limited for the second largest denomination in the world. The term was then changed to Islam albeit the available notations were still felt not enough for the organization of Islamic books. This paper traces and describes the effort by Indonesian librarians and Islamic libraries to improve the notation 297 of the various editions of the DDC since 1973 to 1987. In 1987 the joint declaration between the Minister of Religious Affairs and the Minister of Education and Culture issued an adaptation and expansion of the DDC. This version is widely used especially in public and Islamic-based-schools, Islamic higher education institutions and Islamic colleges, but not in non-Islamic-denomination academic and special libraries. In 2005 the National Library of Indonesia issued its version based on DDC 22nd edition and the details of this version are explained. Based on the various versions, the authors proposed that future adaptation and expansion should be based on the original DDC version. With that adaptation then the proposed expansion, matched with the international usage and practice, could contribute to future DDC editions.